Marketing Mix To Online-Based Consumer Purchase Decisions (Study of Palopo City Grab Transportation Service Users) - Muhammad Aqsa; M. Risal; Firda Jamil (Jurnal Mantik, 2022)
The purpose of this study is to analyze the effect of product, price, place and promotion variables on consumer purchasing decisions for users of online transportation-based Grab in Palopo city. The data used in this research is primary data and the technique of using the data in this research is using a questionnaire. The number of samples from the population in this study was 81 samples. The data analysis technique in this study is multiple linear regression and data processing using the SPSS 21 application. The findings in the research that has been conducted reveal that the variables in this study, namely product, price, place and promotion variables have a significant and positive influence both partially and simultaneously on consumer purchasing decisions using online transportation service users Grab in Palopo City.